Analisa Konsentrasi NaOH dan Temperatur Pemanasan Terhadap Kadar Selulosa dan Kadar Lignin dari Batang Pisang Klutuk Menggunakan Alat Delignifikasi sebagai Bahan Baku Pembuatan Bioetanol. - Rafit Arjeni; Abu Hasan; Aida Syarif (LPPM Politeknik Jambi, 2022)
Indonesia is a country with the largest energy consumption in southeast asia and fifth in asia pacific in primary energy consumption, after a chinese, india, japan, and south korea. If considered sectorally, so having the greatest share of the transportation sector, is as much as 42%, higher than the industrial sector with of 36. Hence the need of the use of environmentally friendly alternative energy and new and renewable energy ( ebt bioetanol ) as. Bioetanol can come from organic waste as klutuk stems of a banana tree. To research it will study and to making delignifikasi adsorbsi klutuk bioetanol of a banana stem. To research will be done study delignifikasi and adsorbsi to making bioetanol of a banana stem klutuk. First, perform the process pratreatmen and delignifikasi in a banana stem klutuk with variations konsetrasi naoh 10%, 20%, 30% and temperature warming namely 100oC, 125oC, 150oC, 175oC, and 100oC. At the delignifikasi this can be said that on the concentration naoh 10% in 150oC, warming temperatures produce levels of cellulose and lignin best, to the cellulose and lignin 81,3% levels 10,1%. A banana stem fiber that has been in delignifikasi, next will be done and also hydrolysis fermentation to produce bioetanol. Bioetanol produced the application will be done distillation to separate bioetanol and water. Bioetanol next analysis used a gcms and obtained bioetanol 80,34%.